2021
DOI: 10.1086/714962
|View full text |Cite
|
Sign up to set email alerts
|

Equitable, Quality Education for Ethnic Minority Students? A Case of “Positive Deviance” in Vietnam

Abstract: Vietnam has achieved near-universal access to compulsory schooling over the past two decades. However, inequalities between ethnic majority and minority students are stark at post-compulsory levels, where progression is selective based on academic criteria and ability to pay. In this article, we adopt a mixed-methods approach to examine quality and equity for ethnic minority students in upper secondary education. Across five provinces, we find that ethnic minority students attend "less effective" upper seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Zaidi et al (2012) used the PDA to identify high-performing medical school students' successful behaviours and disseminate them to ordinary students to improve their overall clinical performance. Iyer et al (2021) revealed that while most schools in Vietnam that enrolled low-income ethnic minority students made less progress compared with schools in wealthier provinces, one school was more effective than others. The positive deviance, in this case, was the school's free boarding policy for ethnic minority students, which liberated them from chores at home and the long commute to the school and encouraged them to place a high value on their learning.…”
Section: The Positive Deviance Approach and Its Application In Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Zaidi et al (2012) used the PDA to identify high-performing medical school students' successful behaviours and disseminate them to ordinary students to improve their overall clinical performance. Iyer et al (2021) revealed that while most schools in Vietnam that enrolled low-income ethnic minority students made less progress compared with schools in wealthier provinces, one school was more effective than others. The positive deviance, in this case, was the school's free boarding policy for ethnic minority students, which liberated them from chores at home and the long commute to the school and encouraged them to place a high value on their learning.…”
Section: The Positive Deviance Approach and Its Application In Educationmentioning
confidence: 99%
“…The positive deviance approach (PDA) can be used to identify their successful behavioural patterns within the context of ERT. The purpose of using the PDA is to discover demonstrable behaviours that community members can use in difficult situations (Positive Deviance Initiative, 2010).This approach is found to be useful for identifying successful behaviours of medical school students (Zaidi et al, 2012) and students in rural schools in Vietnam (Iyer et al, 2021). By using the PDA, we hope to suggest actions and policies that faculty members and higher education institutions can take to solve unexpected problems in the future.…”
Section: Introductionmentioning
confidence: 99%